2011
DOI: 10.1177/0044118x11421941
|View full text |Cite
|
Sign up to set email alerts
|

Impulsivity, School Context, and School Misconduct

Abstract: Impulsivity holds a central place in the explanations of adolescent delinquency. Recent research suggests that neighborhood characteristics, particularly SES (socioeconomic status), perceived supervision, and collective efficacy, moderate the association between impulsivity and delinquency. However, findings to date have been equivocal, and the relationships between social context, impulsivity, and delinquency remain an open question. This study builds on the current literature by examining the moderating infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
30
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 37 publications
(56 reference statements)
3
30
0
1
Order By: Relevance
“…Furthermore, only one prior study has examined moderating effects of impulsivity on relationships between promotive factors from the school context and adolescent problem behaviors. Findings from this study indicated that aggregated levels of school connectedness (as an indicator of school climate) were more strongly associated with decreased likelihood of carrying weapons to school among youth reporting higher levels of impulsivity (Vogel & Barton, 2011). …”
mentioning
confidence: 78%
See 2 more Smart Citations
“…Furthermore, only one prior study has examined moderating effects of impulsivity on relationships between promotive factors from the school context and adolescent problem behaviors. Findings from this study indicated that aggregated levels of school connectedness (as an indicator of school climate) were more strongly associated with decreased likelihood of carrying weapons to school among youth reporting higher levels of impulsivity (Vogel & Barton, 2011). …”
mentioning
confidence: 78%
“…Although there is growing evidence that impulsive youth are more susceptible to environmental influences than non-impulsive youth, few studies have been based on socioeconomically, racially, and ethnically diverse samples of adolescents (c.f., Vogel & Barton, 2011), limiting generalization of results. Additionally, there is a clear need for more research examining moderating effects of impulsivity on youth’s susceptibility to promotive environmental factors, especially those from school and neighborhood contexts.…”
Section: Limitations Of Prior Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…First, principle components analysis revealed that this is the only scale to capture a single latent construct. Second, this measure is consistent with prior person-context work using the Add Health survey (Vazsonyi et al 2006;Vogel and Barton 2013). In an effort to more fully capture the multifaceted nature of impulsivity, a series of supplemental models were also estimated by substituting the alternative measures for the four-item measure described here.…”
Section: Declaration Of Conflicting Interestsmentioning
confidence: 96%
“…This emerging perspective, typically referred to as ''person-context'' research, is based on the premise that behavioral outcomes are not the result of individual or environmental factors but are dependent on who is in what environment (Messner and Zimmerman 2012;Wikström 2004). The general consensus is that risk factors such as impulsivity, exposure to violence, and peer group processes are not fixed predictors of criminal behavior; rather, they are contingent on the characteristics of broader ecological contexts, such as the school one attends or neighborhood in which one resides (e.g., Gibson 2012;Lynam et al 2000;Vazsonyi, Cleveland, and Wiebe 2006;Vogel and Barton 2013;Zimmerman andMessner 2010, 2011;Zimmerman et al 2015).…”
Section: Introductionmentioning
confidence: 99%